Pulmonary hypertension and breathlessness: is it a combination we can ignore?. Issue 2 (February 2014) - Strange, G.; Williams, T.; Kermeen, F.; Whyte, K.; Keogh, A.
Abstract On 5 May 2013 it was World Pulmonary Hypertension (PHT) Day marking three decades on from the first reported deaths in an epidemic because of toxic rapeseed (canola) oil. This epidemic provided the impetus to the first World Health Organization to set up a world symposia. World leaders of PHT met for the fifth time in Nice, France in February 2013. Although we wait the official proceedings, this meeting provides us opportunity to reflect on the current situation in Australia and New Zealand, and examine the implications for our two countries. PHT remains difficult to identify, delays in patient diagnosis persist, and breathlessness remains dominant in the diagnosis of all causes of PHT. This review examines some of the recent changes in diagnosis, our understanding of the emerging expanding epidemiology data and the patient's journeys through the healthcare system. We also review the current treatment options on monotherapy and in poly‐pharmacy or combination therapy, along with the strategic management implications of the lack of funded combination therapy associated with prognosis.